Análisis financiero y económico: rendimiento en la utilización del leasing financiero en la empresa de transportes inversiones Batel S.A.C. - Yupanqui Polo, Jahaira Elizabeth (2011)
Given the current conditions of economic crisis, lack of liquidity and guarantee of the companies, we see the need to look for the alternative of financing more suitable to acquire the necessary means to obtain the profitability planned, so that motivated the development of this work research. The work was developed in the province of Trujillo on the basis of Transport Investment Company Batel S.A.C., in come generating third category, of which data were obtained which allowed to reach final conclusions, applying technology and research bibliographic aid could be concluded. During the development of research work, we found that there are three alternatives of financing: Loan, counted and leasing; being most recommended leasing that started from the’70s is emerges as an alternative means of financing the loan, especially for the acquisition of fixed assets and now it's necessary to use both by the lack of guarantees for its economic benefits, financial and tax offering, so recommends its dissemination and use.